Lactose-Astaxanthin Increases Green Jungle Fowl’s Sperm Motility and Reduces Sperm DNA Fragmentation During 5o Celsius Storage - Bebas, Wayan; Pemayun, Tjok Gede Oka; Damriyasa, I Made; Astawa, I Nyoman Mantik (BALI MEDICAL JOURNAL; Vol 4 No 3 (2015), 2015)
Background: Good quality of semen is required for artificial insemination technology in ex-situ conservation efforts of green jungle fowl. This study was aimed to investigate semen quality of green jungle fowl during storage at 5oC for 48 hours with the addition of combination lactose astaxanthin in egg yolk phosphate dilution. Method: The semen used in the study was collected from eight healthy male green jungle fowls by using massage techniques. The semen quality was analyzed with macroscopic and microscopic examinations. The semen was diluted with egg yolk phosphate with the addition of 0.6% lactose, 0,004% astaxanthin and combination 0.6% Laktose-0,004% astaxanthin, and was stored at 5oC for 48 hours. Following 48-hour treatment, the semen quality was evaluated based on its progressive motility, and DNA fragmentation. Data were firstly analyzed by using analysis of variance (ANOVA), and were then proceeded by using Duncan Multiple Range test. Results: The results showed that the progressive motilities of semen diluted in 0.6% lactose combined with astaxanthin 0.004% %, (79,66 + 1.50%) was significantly higher than those diluted in 0.6% lactose (66,77 + 2.16%,) and in astaxanthin 0.004% (68,11 + 3.01 %). The DNA fragmentation of semen diluted inn 0.6% lactose combined with astaxanthin 0.004% %, (7,55 + 1,66%) was significantly lower than those diluted in 0.6% lactose (12,33 + 1,93%) and in astaxanthin 0.004% (13,55 + 1,81%). Conclusions: In conclusion, the combination of l 0.6% lactose -astaxanthin 0.004% showed the best results for progressive motility, and DNA fragmentation.
Keywords: lactose, astaxanthin, green jungle fowl semen quality, storage at 5oC